Resources to respond: A career construction theory perspective on demands, adaptability, and career crafting - Nalis, Irina; Kubicek, Bettina; Korunka, Christian (The Career development quarterly, 2022)
This study tests and extends the career construction theory's model of adaptation and provides valuable insights into the interplay of agency and structure in career self‐management. It studies the interactive effect of career adaptability resources with intensified career demands on career crafting by examination of structural predictors for adapting responses, and the role of career adaptability as a moderator between intensified demands and career crafting responses. Using a representative sample of the German working population (N = 2000), the authors test the model with structural equation modeling. Latent structure analysis showed that each of the four career adaptabilities strengthens the relationship between intensified career demands and the career crafting responses of goal setting/networking and reflection. It suggests to focus strongly on the development of career resources in order to enable career crafting.